PELUANG USAHA KULINER KHAS MADURA BERBAHAN SINGKONG PADA AGROINDUSTRI KREPEK TETTE DI PAMEKASAN - Badrut Tamami, Novi Diana (Agriekonomika, 2013)
ABSTRACTFAO and World Bankâs predictions about the threat of food crisis in 2025 had a special attention from the many countries over the world. Indonesia had several programs to keep the food security. One of this campaigns was changing consumer behavior from rice to yam group. In this program cassava was chosen as a national strategic food like rice and corn. One of the food agroindustry from cassava that have a potential market is Krepek Tette. But, This Business Opportunity of Maduraness traditional food had not cultivated seriously. Krepek Tetteâs Agroindustry is just a side job with small scale production for local. The aim of this study was to calculated the economic value added and the profit opportunity by Krepek Tetteâs Agroindustry so that this activity become one of the local livelihood choice. The Hayamiâs value added was used to analysed this research. The result of this study shows in once production of Krepek tetteâs agroindustry is small scale but feasible and prifitable.Keywords: Cassava, Agroindustry, Hayami, Value Added.